PENGARUH KEPEMIMPINAN DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA PT. TUJUH INSAN MADANI JAKARTA BARAT - Roni Fadli (KOLONI, 2022)
This study aims to determine the effect of leadership and work discipline on employee performance at PT. Seven Civilians in West Jakarta. The method used in this study is quantitative associative and data were collected through questionnaires distributed via google form. Total population and sample are 56 respondents. The analysis used includes: validity test, reliability test, normality test, heteroscedasticity test, multicollinearity test, simple linear regression analysis, multiple linear regression analysis, correlation coefficient analysis, coefficient of determination analysis, t test and f test. The results showed that Leadership (X1) had a positive and significant effect on Employee Performance (Y) with the regression equation Y= 8.134 + 0.410 X1. The results of the t-test obtained tcount > ttable (8,540 > 1,677) or with a significant probability value of 0.000 < 0.05, then H0 is rejected and H1 is accepted. Work Discipline (X2) has a positive and significant effect on employee performance (Y) with the regression equation Y = 9.973 + 0.393 X2. And with the results of the t-test obtained tcount < ttable (4,066 <1,677) or with a significant probability value of 0.100> 0.05 then H0 is accepted and H2 is rejected. The results of the simultaneous test showed that Leadership (X1) and Work Discipline (X2) had a positive and significant effect on Employee Performance (Y) with the regression equation Y= 8.134 + 0.410 (X1) + 0.393 (X2). And the results of the F test obtained the value of Fcount > Ftable (21,090 > 2,800) or with a significant probability of 0.000 < 0.05. The contribution given by leadership and work discipline to employee performance is 57.5%.  Keywords:  Leadership, Work Discipline, and Employee Performance